The Mammals - Carrington, Richard; Editors of TIME-LIFE BOOKS (Time-Life Books : Hong Kong, 1980)
The Mammals provides an accessible and richly illustrated introduction to the diverse world of mammals. Topics covered include: Evolution and classification of mammal species Anatomy and physiology of mammals Reproductive strategies and migration patterns Ecological roles and human interactions with mammals Special focus on various mammal families and their adaptations The volume features full-color photographs, diagrams, and picture essays that enhance understanding of the subject matter.
Keywords: Mammals